2022
DOI: 10.1007/s10877-022-00825-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of preoxygenation by conventional face mask versus non-invasive ventilation in morbidly obese patients: measurable by the oxygen-reserve index?

Abstract: Preoxygenation is a crucial manoeuvre for patients’ safety, particularly for morbidly obese patients due to their reduced pulmonary reserve and increased risk for difficult airway situations. The oxygen reserve index (ORI™) was recently introduced as a new parameter of multiple wavelength pulse oximetry and has been advocated to allow assessment of hyperoxia [quantified by the resulting arterial oxygen partial pressure (PaO2)]. This study investigates if ORI can be used to evaluate the impact of two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Some studies have indicated that this type of therapy has little effect on the gastrointestinal tract and can effectively correct body hypoxia [17,18]. However, research has also proven that mechanical ventilation alone can be insufficient in terms of secretion drainage compensation, thus creating a limitation of its single application [19,20]. Non-invasive sequential ventilation therapy is based on the use of an invasive mechanical ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that this type of therapy has little effect on the gastrointestinal tract and can effectively correct body hypoxia [17,18]. However, research has also proven that mechanical ventilation alone can be insufficient in terms of secretion drainage compensation, thus creating a limitation of its single application [19,20]. Non-invasive sequential ventilation therapy is based on the use of an invasive mechanical ventilator.…”
Section: Discussionmentioning
confidence: 99%